Perusakan Komponen Kendaraan Rental: Wanprestasi Dalam Kontrak Sewa Kendaraan - I Putu Agus Gilang Sedana Putra; A.A. Gede Duwira Hadi Santosa (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
A stipulation born between two or more parties that is legally guaranteed and creates specific rights and obligations for each individual is the definition of a contract. In the law of obligations, a contract is considered a fundamental instrument that allows individuals or entities to manage their relationships with each other. However, in practice, breaches or non-compliances with what has been agreed upon, known as "default", are not uncommon. Default occurs when someone bound by an agreement does not fulfill their obligations in accordance with the content agreed upon in a contract, whether in the form of a direct violation or not taking the necessary actions. The impact of a default can be in the form of material losses, immaterial losses, or both. Resolving defaults typically involves negotiations between parties, mediation, arbitration, or even formal legal routes through the courts. It is important for contracting parties to understand their rights and obligations to prevent defaults and reduce the risk of disputes in the future.